2018
DOI: 10.18632/oncotarget.24106
|View full text |Cite|
|
Sign up to set email alerts
|

WITHDRAWN: Sarcopenia as a leading risk factor for erosive esophagitis

Abstract: Backgrounds: Obesity is an established risk factor for erosive esophagitis. Yet, the associations of sarcopenia and obesity with erosive esophagitis remain unclear. We studied the associations of obesity, sarcopenia, and sarcopenic obesity with the risk of erosive esophagitis in a large number of asymptomatic men and women. Materials and Methods: We conducted a cross-sectional study of 32,762 asymptomatic adults undergoing routine health checkups including screening endoscopy, between August 2006 and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Gastric cancer is one of the main culprits affecting the incidence rate and mortality of cancer in China. And this study is currently the largest evaluative study conducted in China on the impact of tumor size and cancer survival rate [11] .A relative study in Korean for patients who finished curative surgery for differentiated minute submucosal cancer, the final results demonstrated that one-dimensional tumor size > 2.9 cm and two-dimensional tumor size more than 8.3 cm2 have higher risk of postoperative morbidity and mortality [12] . Another study based on the SEER database showed that compared to the small size (≤ 2.5 cm) tumor group, the prognosis of the large size (≥ 5.3 cm) tumor group and the medium size (2.6-5.2 cm) tumor group was generally poor.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Gastric cancer is one of the main culprits affecting the incidence rate and mortality of cancer in China. And this study is currently the largest evaluative study conducted in China on the impact of tumor size and cancer survival rate [11] .A relative study in Korean for patients who finished curative surgery for differentiated minute submucosal cancer, the final results demonstrated that one-dimensional tumor size > 2.9 cm and two-dimensional tumor size more than 8.3 cm2 have higher risk of postoperative morbidity and mortality [12] . Another study based on the SEER database showed that compared to the small size (≤ 2.5 cm) tumor group, the prognosis of the large size (≥ 5.3 cm) tumor group and the medium size (2.6-5.2 cm) tumor group was generally poor.…”
Section: Discussionmentioning
confidence: 84%
“…The two-dimensional size of these patients' tumors is>8.9 cm 2 , which also increases the risk of lymph node metastasis. [12] . Another related study involved a total of 146 patients.…”
Section: Discussionmentioning
confidence: 99%